Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

The Emergence and Promise of Functional Chemogeography of Organic Matter - Ang Hu; James Stegen; Andrew J. Tanentzap; Jianjun Wang (Global Change Biology, 2025)
Organisms in ecosystems continuously release a myriad of organic matter molecules that undergo microbial and abiotic transformation, processes that critically influence carbon storage and climate feedbacks. Yet, a systematic understanding of what determines the transformation and persistence of organic matter across spatiotemporal scales remains elusive. We propose an emerging framework, termed “functional chemogeography,” to understand transformation and persistence of organic matter based on the chemical traits of molecules. This framework extends beyond a sole focus on intrinsic traits, which remain relatively constant across spatiotemporal scales, to emphasize extrinsic traits such as biochemical transformations and environmental responses, which vary spatiotemporally and are shaped by both intrinsic traits and the environment. When upscaled to the assemblage level using functional diversity indices, these extrinsic traits reveal a significant, and in some cases superior, capacity than intrinsic traits to explain biogeochemical processes, as demonstrated through a case study of dissolved organic matter in China's lakes. By integrating trait‐based perspectives into predictive models, this framework helps bridge chemical complexity with ecosystem biogeochemistry, thereby advancing our ability to predict the fate of global organic carbon under environmental change.

Emerging technologies, policies and challenges toward implementing sustainable aviation fuel (SAF) - Jason Ik Cheng Lau; Yu Si Wang; Tiffany Ang; James Chai Fah Seo; Sabeeha N.B.A. Khadaroo; Jiuan Jing Chew; Andrew Ng Kay Lup; Jaka Sunarso (Biomass and Bioenergy, 2024)

Temperature sensitivity of organic carbon decomposition in lake sediments is mediated by chemodiversity - Shuailong Wen; Ang Hu; Shuyu Jiang; Lei Han; Kyoung‐Soon Jang; Andrew J. Tanentzap; Jicheng Zhong; Jianjun Wang (Global Change Biology, 2024)
Organic carbon decomposition in lake sediments contributes substantially to the global carbon cycle and is strongly affected by temperature. However, the magnitude of temperature sensitivity ( Q 10 ) of decomposition and the underlying factors remain unclear at the continental scale. Carbon quality temperature (CQT) hypothesis asserts that less reactive and more recalcitrant molecules tend to have higher temperature sensitivities, but its support is challenged by complex composition of organic matter and environmental constraints. Here, we quantified Q 10 of the sediments across 50 freshwater ecosystems along a 3500 km north–south transect, and characterized the quality of sediment dissolved organic carbon with chemodiversity reflected in molecular richness, functional traits (i.e., molecular weight, bioavailability, etc.) and composition. We further included classic environmental variables, such as climatic, physicochemical and microbial factors, to explore how Q 10 is constrained by these factors or carbon quality. We found that Q 10 varied greatly across lakes, with the mean value of 1.78 ± 0.62, but showed nonsignificant latitudinal pattern. Q 10 was primarily predicted by chemodiversity and showed an increasing trend with the biochemical recalcitrance indicated by traits such as aromaticity and standard Gibb's Free Energy at both molecular and compositional levels. This suggests that carbon quality is the crucial determinant of Q 10 in lakes, supporting the CQT hypothesis. Moreover, Q 10 decreased linearly with the increase of molecular richness, implying that the resistance of decomposition to warming is associated with higher molecular diversity. Compared with the structural equation model containing only environmental variables, inclusion of chemodiversity increased 32.8% of the explained variation in Q 10 , and chemodiversity was the only driver showing direct effects. Collectively, this study illustrates the importance of chemodiversity in shaping the pattern of Q 10 , and has significant implications for accurately predicting the carbon turnover in lake ecosystems in the context of global warming.

Uncertainty Quantification in Tomographic Inversion of Near-Surface Seismic Refraction Data - Ang Li; Dario Grana; Andrew D. Parsekian; Brad Carr (Mathematical Geosciences, 2024)

Exploring the internal textures and physical properties of digitate sinter in hot springs: Implications for remote sampling on Mars - Ema E. Nersezova; Michael C. Rowe; Kathleen A. Campbell; Andrew Ang; Steve Matthews; Steven W. Ruff; Ashok Meghwal; Ludmila Adam; Niamh Galligan; Thomas Loho (Planetary and Space Science, 2023)

Correction: Geostatistical Rock Physics Inversion for Predicting the Spatial Distribution of Porosity and Saturation in the Critical Zone - Dario Grana; Andrew D. Parsekian; Brady A. Flinchum; Russell P. Callahan; Natalie Y. Smeltz; Ang Li; Jorden L. Hayes; Brad J. Carr; Kamini Singha; Clifford S. Riebe; W. Steven Holbrook (Mathematical Geosciences, 2022)

Geostatistical Rock Physics Inversion for Predicting the Spatial Distribution of Porosity and Saturation in the Critical Zone - Dario Grana; Andrew D. Parsekian; Brady A. Flinchum; Russell P. Callahan; Natalie Y. Smeltz; Ang Li; Jorden L. Hayes; Brad J. Carr; Kamini Singha; Clifford S. Riebe; W. Steven Holbrook (Mathematical Geosciences, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Vascular KATP channels protect from cardiac dysfunction and preserve cardiac metabolism during endotoxemia - Qadeer Aziz; Jianmin Chen; Amie J Moyes; Yiwen Li; Naomi A Anderson; Richard Ang; Dunja Aksentijevic; Sonia Sebastian; Adrian J Hobbs; Christoph Thiemermann; Andrew Tinker (Journal of Molecular Medicine, 2020)
K ATP channels in the vasculature composed of Kir6.1 regulate vascular tone and may contribute to the pathogenesis of endotoxemia. We used mice with cell-specific deletion of Kir6.1 in smooth muscle (smKO) and endothelium (eKO) to investigate this question. We found that smKO mice had a significant survival disadvantage compared with their littermate controls when treated with a sub-lethal dose of lipopolysaccharide (LPS). All cohorts of mice became hypotensive following bacterial LPS administration; however, mean arterial pressure in WT mice recovered to normal levels, whereas smKO struggled to overcome LPS-induced hypotension. In vivo and ex vivo investigations revealed pronounced cardiac dysfunction in LPS-treated smKO, but not in eKO mice. Similar results were observed in a cecal slurry injection model. Metabolomic profiling of hearts revealed significantly reduced levels of metabolites involved in redox/energetics, TCA cycle, lipid/fatty acid and amino acid metabolism. Vascular smooth muscle-localised K ATP channels have a critical role in the response to systemic infection by normalising cardiac function and haemodynamics through metabolic homeostasis. Key messages • Mice lacking vascular K ATP channels are more susceptible to death from infection. • Absence of smooth muscle K ATP channels depresses cardiac function during infection. • Cardiac dysfunction is accompanied by profound changes in cellular metabolites. • Findings from this study suggest a protective role for vascular K ATP channels in response to systemic infection.

A comparison of the antifouling performance of air plasma spray (APS) ceramic and high velocity oxygen fuel (HVOF) coatings for use in marine hydraulic applications - Richard Piola; Andrew S. M. Ang; Matthew Leigh; Scott A. Wade (Biofouling, 2018)

Oxoiron(IV) complexes as synthons for the assembly of heterobimetallic centers such as the Fe/Mn active site of Class Ic ribonucleotide reductases - Ang Zhou; Patrick M. Crossland; Apparao Draksharapu; Andrew J. Jasniewski; Scott T. Kleespies; Lawrence Que (JBIC Journal of Biological Inorganic Chemistry, 2018)

Efficient Adsorptive Removal of Humic Acid from Water Using Zeolitic Imidazole Framework-8 (ZIF-8) - Kun-Yi Andrew Lin; Hsuan-Ang Chang (Water, Air, & Soil Pollution, 2015)

TM4SF1: a tetraspanin-like protein necessary for nanopodia formation and endothelial cell migration - Andrew Zukauskas; Anne Merley; Dan Li; Lay-Hong Ang; Tracey E. Sciuto; Samantha Salman; Ann M. Dvorak; Harold F. Dvorak; Shou-Ching Shih Jaminet (Angiogenesis, 2011)